Interfacial charge transfer and enhanced photocatalytic mechanisms for Pt nanoparticles loaded onto sulfur-doped g-C3N4 in H2 evolution. (December 2021) - Li, Zizhen; Yao, Yuan; Gao, Xinyu; Bai, Hongcun; Meng, Xiangchao
Abstract: C3 N4 exhibits great research potential in photocatalytic hydrogen evolution. Herein, sulfur is doped into C3 N4 (SCN) by using thiourea as the precursor. The platinum (Pt) nanoparticles (NPs) are photo-deposited onto the surface of S-CN. Photocatalytic activity in H2 evolution for C3 N4 is improved from 0 to 56.58 μmol/h/gcat  after sulfur doping, and to 742.19 μmol/h/gcat  with the modifications of sulfur and Pt NPs. The enhancement in the photocatalytic hydrogen production may be due to the following: (1) the dope of sulfur can optimize the band structure and provide more reactive site for C3 N4, (2) the porous morphology of S-CN enhanced the light-harvesting ability of C3 N4, (3) Pt NPs with the surface plasmonic resonance effect are capable of absorbing more photons of visible light, and (4) Pt acts as a reservoir of photogenerated charge carriers, inhibiting its recombination. Enhancement mechanism has been deeply explored and comprehensively discussed in this work. Graphical abstract: Image 1 Highlights: Pt nanoparticles loaded on S-doped C3 N4 have been successfully prepared. As-prepared composite exhibited excellent photocatalytic activity in H2 evolution. Possible mechanism of the enhancement has been comprehensively and deeply explored.